TINJAUAN BEBAN KERJA PETUGAS ASSEMBLING ANALISIS REKAM MEDIS RAWAT INAP DENGAN METODE WISN (WORK LOAD INDICATOR STAFF NEEDS) GUNA MENUNJANG EFEKTIFITAS KERJA DI RSUP DR. HASAN SADIKIN BANDUNG - Suharto Harto Harto; Luqmanul Hakim (UPPM Politeknik TEDC Bandung, 2020)
Based on preliminary study conducted on 13 to 14 January 2020 in RSUP Dr. Hasan Sadikin Bandung with sample 1 officer assembling the analysis of hospitalization medical SMF child health. Assembling processing time can complete 41 medical record files with an average of 5.51 minutes/1 Medical record file for 3 hours 46 minutes or 226 minutes, and analysis of manual or paper-based medical records can complete the 41 medical record file with an average of 6.09 minutes/1 Medical record file for 4 hours 10 minutes or 250 minutes. The purpose of this research is to know and add insight into calculating the personnel workload assembling an inpatient medical record analysis based on WISN method in RSUP Dr. Hasan Sadikin Bandung.The research method used is a descriptive method with a quantitative analysis approach. Data collection techniques are with interviews, observations, and documentation studies. Research instruments used stationery, stopwatches, calculators, and interviewees. The result of the research of HR needs officers assembling the analysis of the inpatient medical record with the WISN method is 8.65 people or rounded 9 people and already correspond to the amount of field but need to equalization between officers assembling with analysis. While the effectiveness of officers assembling the analysis of hospitalization medical record has not been effective due to lack of personnel discipline against the specified working hours. The author suggests that the SOP Rereview, holding education and training at least 1 year to improve quality, quantity and discipline in a better working way.